Analysis of Activity-Based Costing (ABC) Implementation for Inpatient Operational Cost Control in 2025 - Ongky Harianto; Ermi Girsang; Sri Lestari Ramadhani Nasution (The International Journal of Medical Science and Health Research, 2026)
Background: Hospitals require accurate cost information to set service tariffs, prepare budgets, and control operational costs. At RS Pratama Krayan, inpatient tariff determination may still create cost distortion because it has not fully applied an activity-based approach. Objective: This study aimed to analyze the implementation of Activity Based Costing (ABC) in controlling inpatient operational costs at RS Pratama Krayan, North Kalimantan, in 2025. Method: This study employed a quantitative descriptive method with a case study approach. Data were collected through documentation and interviews, then analyzed using ABC procedures, including activity identification, cost pooling, cost driver determination, activity rate calculation, and cost allocation to each inpatient class to obtain the unit cost. Results: The findings identified nine major cost activities with a total inpatient operational cost of IDR 2,744,000,000. Activity rates were calculated using inpatient days, room area, and electricity consumption as cost drivers. ABC calculation produced inpatient unit costs per day of IDR 179,494 for VIP, IDR 107,782 for Class I, IDR 88,608 for Class II, and IDR 86,881 for Class III. All values were lower than the existing tariffs, with reductions of 48.7% for VIP, 46.1% for Class I, 50.8% for Class II, and 42.1% for Class III. Conclusion: The implementation of ABC provides more detailed, proportional, and transparent inpatient cost information and can serve as a basis for tariff evaluation and hospital operational cost control.